CFP: Inter- and Transcultural Heritage. Conflicts, Overlaps, Coexistence - Cheryl (Publishing in the Archives Profession, 2025)
Due July 20: Lucian Blaga University of Sibiu, as part of the FORTHEM Alliance, invites scholars, researchers, and practitioners to submit proposals for the upcoming Cultural Heritage Lab International Conference, dedicated to exploring cultural heritage within, across, and beyond the European Union’s borders. This year’s theme investigates the dynamics of intercultural, interethnic, and social interactions—especially in regions where boundaries (geographical, political, linguistic, or symbolic) are fluid and contested.
Worldwide